Research advance of risk assessment of virus-resistant transgenic plants - NIU Yan-bing; LI Gui-xin (浙江大学学报. 农业与生命科学版, 2004)
Virus-resistant transgenic plants (VRTPs) hold the promise of enormous benefit and great practical potential for agriculture. However, with the increase in quantity of filed release and commercialization, questions concerning the potential risk of VRTPs have been gradually raised. The main possible risks include: recombination, synergism and heterologous encapsidation. Based on mechanism for resulting in risk, effective methods have been developed to eliminate the possible risks.